Pengaruh Celebrity Endorser, Citra Merek dan Kualitas Produk terhadap Minat Beli Kosmetik Wardah di Rimbo Bujang Kabupaten Tebo - Agista Bella Rahmanita; Yudhi Novriansyah; Khairun A Roni (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This Research to determine the influence of Celebrity Endorser, Brand Image, and Product Quality on the Purchase Intention of Wardah Cosmetics in Rimbo Bujang, Tebo Regency. The research population consists of all consumers of Wardah cosmetic products, which is an unlimited number, where a sample of 100 respondents was selected using the Purposive Sampling technique. (Sampel bertujuan). Based on the data processing results using SPSS, it was found that, partially, Celebrity Endorser has a positive and significant effect on the purchase interest in Wardah Cosmetics. Brand Image has a positive and significant effect on the purchase interest in Wardah Cosmetics, and Product Quality has a positive and significant effect on the purchase interest in Wardah Cosmetics. Simultaneously, Celebrity Endorser, Brand Image, and Product Quality together have a positive and significant effect on the purchase interest.